Features of the Development of a Teenager's Subjectivity in Interaction with the Natural Environment in a Children's Educational and Health Camp - Kamnev A.N; Mikhailova T.A (Moscow State University of Psychology and Education, 2021)
The work shows that only a certain psychological and pedagogical complex, consisting of a convenient educational platform, using objects of nature in the pedagogical process; correctly selected psychological and pedagogical methods and a trained teaching staff will be able to contribute to the search and implementation of new psychological and pedagogical approaches used for the development of personality and subjectivity of adolescents. The most convenient site for these purposes may be a children's health camp. This educational platform is unique in terms of balancing lesson and extracurricular activities, providing opportunities for communicative interaction between peers, as well as adolescents and adults. It is also important that the environment of a country camp provides a child with the opportunity to discover those natural phenomena that could only be learned theoretically in the classroom. By contributing to the implementation of interdisciplinary environmental research projects, the camp creates conditions for the development of the adolescent's subjectivity in interaction with the natural environment. Receiving new skills and abilities in the camp, the child moves to a new level of education, and accordingly acquires new personal experience. Thus, the presented work shows that it is necessary to rethink the importance of children's health camps. While retaining the traditional functions of health improvement, recreation and entertainment, camps should provide and compensate for the educational and educational functions of modern school education. Camp activities should be productive.